Financial Literacy in The Sustainability of MSME’s Businesses in Katinggolan Sub-District, East Tondano District, Minahasa Regency - Emor, Andreas; Sendouw, Recky H. E.; Tarore, Steven (Technium Social Sciences Journal, 2023)
With the existence of Micro, Small, and Medium Enterprises (MSMEs), people can utilize all existing skills for economic survival, both individually and as a group. Good financial management can be measured by the level of financial literacy one has. The aim of this research is to find out, describe, analyze, and explain Financial Literacy in the sustainability of MSME businesses in Katinggolan Sub-District, East Tondano District, Minahasa Regency. The research method used is a qualitative method with a source selection technique, namely snowball sampling. The data collection technique is a triangulation technique: observation, interviews, and documentation studies. The research results show that in order to support the sustainability of MSMEs in Katinggolan sub-district, Tondano Timur, Minahasa, financial literacy education for the community still needs to be improved, especially in terms of 1) recording and bookkeeping; 2) understanding financial reports; 3) wise investment approach; 4) network development and collaboration; 5) regular evaluation and adjustment of financial performance; 6) financial developments and industry trends.